Formation Mechanism of Knowledge Stickiness in the Collaborative Innovation of Industry-University-Research - Feng Zhang; Guoxin Liu*; Yu Wu (Tehnički Vjesnik, 2020)
In the context of deepening the cooperation of Industry-University-Research (IUR), enterprises must gain competitive advantage by transferring external knowledge to the enterprise for knowledge appreciation. Based on the knowledge stickiness encountered in the process of knowledge transfer in the collaborative innovation of IUR, the formation process and causes of knowledge stickiness are analyzed. In this study, the knowledge flow model based on heat conduction theory was proposed. The dynamic simulation was carried out using MATLAB software. Results show that the process of knowledge transfer between IUR is the process of continuously realizing knowledge increment and knowledge creation, and knowledge stickiness has a direct impact on the efficiency of knowledge transfer. Strengthening the cognition between IUR, increasing the number of activities between IUR, and creating a collaborative innovation atmosphere between IUR will reduce knowledge stickiness and improve the efficiency of knowledge transfer.